Efficiency of Hybrid Solar Collectors Application in Building Heating Systems - Stepan Shapoval; Yurii Pryshliak; Fedir Ivashchyshyn; Bogdan Gulai; Mariana Kasynets; Stepan Mysak (Energy Engineering and Control Systems)
The article focuses on the use of hybrid solar collectors as one of the ways to increase the efficiency of solar systems in general. The authors consider the design of a solar collector with the arrangement of circulation pipes above the heat-absorbing surface with a transparent coating. A solar system with natural circulation of the heat carrier (water) has been investigated. Based on the research results, a nomogram has been developed to define the relationship between the thermal efficiency coefficient of the solar cover with a transparent coating and the arrangement of pipes of the heat carrier circulation loop above the heat absorber depending on the angles and the intensity of the radiation flux. As a result, a functional dependence is obtained, which allows accurately determining the coefficient of thermal efficiency for specific parameters and input data. This research indicates the need for the use of hybrid solar collectors to ensure efficient collection of solar energy and emphasizes the importance of further research and improvement of the design of elements of such systems to reduce environmental pollution and increase the stability of heating systems.